Design of a power unit of a nuclear power plant with a VVER reactor with an electrical capacity of 1300 MW; Бутаковские чтения - Ahmed Elsayed Abdelsatar Elsayed (Производство тепловой и электрической энергии, 2021)
Заглавие с экрана